Analisis kesiapan penerapan rekam medis elektronik: Sebuah studi kualitatif - Riyanti Riyanti; Arfan Arfan; Eli Zuana (Holistik Jurnal Kesehatan, 2023)
Background: The Ministry of Health of the Republic of Indonesia launched a blueprint for the "2024 Health Digital Transformation Strategy" with the United Nations Development Program (UNDP). The digital transformation strategy focuses on health services for the wider community and is expected to improve the quality of services more evenly throughout Indonesia. With Indonesia's population of around 270 million people, they have the right to receive optimal, easy and informative health services. The 2024 health digital transformation strategy that was launched is also expected to maintain patient safety, reduce hospital costs, both for patients and health facilities, and be able to control health procedures for patients more comprehensively.Purpose: To determine the preparations to implement Electronic Medical Records at Pertamina Bintang Amin Hospital (RSPBA).Method: Qualitative research uses triangulation techniques using observation, interviews and documentation methods. There were 4 contributors to this research information. The key information contributor is the Director of Pertamina Bintang Amin Hospital (RSPBA) and the triangulation information contributors are the Head of Medical Records, Head of IT, and medical records administrator.Results: Pertamina Bintang Amin Hospital (RSPBA) is ready to implement Electronic Medical Records (EMR), with commitment from management, namely the director and a special team formed to implement Electronic Medical Records (EMR). The Director provides full support in the availability of technology, software, hardware and internet networks. The special team formed to implement Electronic Medical Records (EMR) has also carried out outreach and training activities for all users in implementing Electronic Medical Records (EMR), namely the transformation from conventional to electronic with standard operating procedures.Conclusion: Preparations for implementing Electronic Medical Records (EMR) can be carried out at RSPBA with full support from management, stakeholders and the special team that was formed.Suggestion: RSPBA needs to follow up on existing obstacles and carry out regular monitoring, evaluation and monitoring as well as provide feedback to related parties such as users and teams from third parties as partnersKeywords: Electronic Medical Records (EMR); Health Services; Preparation; Standard Operating Procedures Pendahuluan: Kementerian Kesehatan Republik Indonesia meluncurkan blue print atau cetak biru “Strategi Transformasi Digital Kesehatan 2024” bersama United Nations Development Programme (UNDP). Strategi transformasi digital fokus terhadap pelayanan kesehatan untuk masyarakat luas dan diharapkan dapat meningkatkan kualitas layanan yang lebih merata di seluruh Indonesia.Dengan jumlah penduduk Indonesia sekitar 270 juta jiwa berhak mendapatkan layanan kesehatan yang optimal, mudah, dan informatif. Strategi transformasi digital kesehatan 2024 yang diluncurkan juga diharapkan dapat menjaga keselamatan pasien, biaya rumah sakit yang lebih murah, baik untuk pasien dan fasilitas kesehatan, serta dapat mengontrol prosedur kesehatan untuk pasien yang lebih komprehensif.Tujuan: Untuk mengetahui kesiapan penerapan Rekam Medis Elektronik di Rumah Sakit Pertamina Bintang Amin (RSPBA) .Metode: Penelitian kualitatif menggunakan teknik triangulasi dengan menggunakan metode observasi, wawancara dan dokumentasi. Kontributor informasi penelitian ini berjumlah 4 orang. Sebagai kontributor informasi kunci adalah Direktur Rumah Sakit Pertamina Bintang Amin (RSPBA) dan kontributor informasi triangulasi adalah Kepala Rekam Medis, Kepala IT, dan pelaksana rekam medis.Hasil: Rumah Sakit Pertamina Bintang Amin (RSPBA) siap melakukan penerapan RME, dengan adanya komitmen dari manajemen yaitu direktur dan tim khusus yang dibentuk dalam penerapan RME. Direktur memberikan dukungan penuh tersedianya teknologi, software, hardware dan jaringan internet. Tim khusus yang dibentuk dalam penerapan RME juga sudah menjalankan kegiatan sosialisasi dan pelatihan kepada semua user dalam penerapan RME yaitu transformasi dari konvensional ke elektronik dengan SPO.Simpulan: Persiapan penerapan RME dapat dijalankan di RSPBA dengan dukungan penuh dari manajemen, pemangku kepentingan dan tim khusus yang dibentuk.Saran: RSPBA perlu menindaklanjuti kendala yang ada dan melakukan monitoring, evaluasi, dan pemantauan secara rutin serta memberikan umpan balik kepada pihak terkait seperti user dan tim dari pihak ke tiga sebagai mitra